2018
DOI: 10.3389/fpls.2018.01558
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics of Heat-Stress and Ethylene-Mediated Thermotolerance Mechanisms in Tomato Pollen Grains

Abstract: Heat stress is a major cause for yield loss in many crops, including vegetable crops. Even short waves of high temperature, becoming more frequent during recent years, can be detrimental. Pollen development is most heat-sensitive, being the main cause for reduced productivity under heat-stress across a wide range of crops. The molecular mechanisms involved in pollen heat-stress response and thermotolerance are however, not fully understood. Recently, we have demonstrated that ethylene, a gaseous plant hormone,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 85 publications
2
42
0
Order By: Relevance
“…Although, ROS scavenging is key to ensure that heat stress does not damage the sensitive reproductive tissue, ROS‐dependent programmed cell death is essential for successful fertilisation (Suzuki & Katano, ). Some thermo‐protectants including primary metabolites and phyto‐hormones such as ‐aminobutyric acid (mungbean ( Vigna radiate ), Priya et al , ); salicylic acid (rice, Feng et al , ); flavonols (tomato, Muhlemann et al , ); auxin (rice, Zhang et al , ); and ethylene (tomato, Jegadeesan et al , ) continue to be effective in alleviating heat stress damage in pollen. Although, there are no studies in this direction involving pistils per se , a plausible hypothesis would be that the above‐mentioned compounds will have a similar alleviation potential in pistils exposed to heat stress (Box 2).…”
Section: Male and Female Reproductive Organ Viabilitymentioning
confidence: 99%
“…Although, ROS scavenging is key to ensure that heat stress does not damage the sensitive reproductive tissue, ROS‐dependent programmed cell death is essential for successful fertilisation (Suzuki & Katano, ). Some thermo‐protectants including primary metabolites and phyto‐hormones such as ‐aminobutyric acid (mungbean ( Vigna radiate ), Priya et al , ); salicylic acid (rice, Feng et al , ); flavonols (tomato, Muhlemann et al , ); auxin (rice, Zhang et al , ); and ethylene (tomato, Jegadeesan et al , ) continue to be effective in alleviating heat stress damage in pollen. Although, there are no studies in this direction involving pistils per se , a plausible hypothesis would be that the above‐mentioned compounds will have a similar alleviation potential in pistils exposed to heat stress (Box 2).…”
Section: Male and Female Reproductive Organ Viabilitymentioning
confidence: 99%
“…Various proteins such as HSP, those related to anti-oxidant mechanism, and glycolysis were involved in adaption of grape to heat stress as revealed through iTRAQ analysis (Liu et al, 2014). Proteomics analysis of ethylene pre-treated tomato pollen by LC-MS/MS suggested that various proteins help in protecting pollen development and function through higher abundance of protein synthesis and upregulating stress protecting proteins that maintain cellular redox state under heat stress (Jegadeesan et al, 2018). Proteomics analysis by 2-DE technique allowed identification of important heat shock proteins viz., HSP26, HSP16.9, and unknown HSP/Chaperonin contributing to heat stress tolerance in maize (Abou-Deif et al, 2019).…”
Section: Proteomicsmentioning
confidence: 99%
“…Molecular studies have uncovered heat responses in pollen subjected to high temperature similar to other plant cell types including the heat shock response, the unfolded ER protein response or the formation of reactive oxygen species (20). In addition, a number of untargeted transcriptomics, metabolomics, and proteomics studies have been performed to characterize the response of pollen under heat stress conditions at the molecular level (21)(22)(23)(24). However, the limitations of the proteomics and metabolomics technologies compared to highresolution approaches based on next generation sequencing of nucleic acids (NGS) techniques (25), qualify these NGS approaches as very appropriate to gain deeper insight in the response of pollen to heat stress conditions.…”
Section: Introductionmentioning
confidence: 99%